Psychometric Properties of the Exercise Orientation Questionnaire: A Confirmatory Study on Chinese University Students - Jindong Chang; Jindong Chang; Jindong Chang; Jindong Chang; Jindong Chang; Liming Yong; Liming Yong; Yali Yi; Yali Yi; Xiaolei Liu; Hanbing Song; Hanbing Song; et al. (Frontiers Media S.A., 2021)
The Exercise Orientation Questionnaire (EOQ) is a method for evaluating individuals' exercise attitudes and behaviors associated with exercise motivation. A lack of exercise motivation can affect physical activity attitudes, behavior, and action among university students. Physical inactivity may lead to health risks. The purpose of this study was to assess the measurement of psychological properties in the EOQ and to determine the reliability and validity of the EOQ when applied to Chinese university students. A total of 368 university students (male 48.8%) aged between 17 and 23 years (M = 19.60, SD = 1.18) participated in the current study. Confirmatory factor analysis (CFA) and exploratory structural equation modeling (ESEM) were used to verify the factorial validity of the EOQ. The internal consistency coefficient (Cronbach's alpha and McDonald's omega) was used to determine reliability. Multiple regression analysis was used to test concurrent validity. The International Physical Activity Questionnaire (IPAQ) was used to determine the participants' level of physical activity. The range of the subscale coefficient was 0.80-0.89, and the total scale was 0.95, which indicated that the reliability of the EOQ was excellent. The research showed that the initial CFA model of the EOQ had poorly fitting indices. The corrected model after seven residual correlations achieved the setting standard, but the correlation coefficient between some factors exceeded the standard threshold, which indicated that the CFA fitting model was not ideal. ESEM is a combination of exploratory and verifiable analytical techniques. Using ESEM and abbreviated version CFA to analyze the data indicated that the model fitted well [ESEM: TLI = 0.97 > 0.90, CFI = 0.96 > 0.90, SRMR = 0.02 < 0.08, and RMSEA = 0.045 < 0.08 (90% CI 0.033-0.055); CFA: TLI = 0.92 > 0.90, CFI = 0.91 > 0.90, SRMR = 0.08, and RMSEA = 0.06 < 0.08 (90% CI 0.055-0.067)]. The results of multiple regression analysis suggested that the ESEM model was effective in distinguishing the differences between individuals with different levels of physical activity (PAL) and body mass index (BMI). Overall, the Chinese abbreviated version of the EOQ (EOQ-CA) was fond to be a reliable tool for monitoring the exercise attitudes and behaviors of Chinese University students.